Anti-proliferative and cytotoxic activity of rosuvastatin against melanoma cells - Maj, Malgorzata; Czajkowski, Rafal; Zegarska, Barbara; Kowaliszyn, Bogna; Pokrywczynska, Marta; Drewa, Tomasz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Statins are considered potential candidate agents for melanoma chemoprevention. Statin-induced mevalonate pathway inhibition leads to reduction of cholesterol synthesis and also to decreased cellular levels of non-steroidal isoprenoids, geranylgeranyl pyrophosphate and farnesyl pyrophosphate. This results in the impairment of protein prenylation which affects carcinogenesis. Aim : To analyze anti-proliferative and cytotoxic activity of rosuvastatin against melanoma cells. Material and methods : Melanoma cell lines (A375 and WM1552C) and normal fibroblasts (BJ) were used as the primary research material. Cells were treated with rosuvastatin at concentrations ranging from 0.01 µM to 10 µM. Cell viability was analyzed with the use of an MTT assay. Expression of proliferation marker Ki67 was assessed on the basis of immunofluorescence staining. Results: Rosuvastatin reduced A375 and BJ cell viability in a time- and dose-dependent manner. After 72 h incubation, the IC 50 , half maximal inhibitory concentration, was 2.3 µM for melanoma cells and 7.4 µM for normal fibroblasts. In turn, rosuvastatin exhibited relatively lower activity against WM1552C cells. A significant reduction of Ki67 expression was also noted for BJ fibroblasts after prolonged incubation with the tested drug. Conclusions : The results indicate that the anti-melanoma properties of rosuvastatin are highly dependent on the tumor cell line assessed. However, the concentrations required to decrease melanoma cell viability in vitro exceed the plasma concentrations reached in patients treated with rosuvastatin at well-tolerated doses. What is more disturbing, reduction of proliferation and viability observed in BJ fibroblasts indicated that rosuvastatin at high doses may be toxic for normal cells.